Acceptability and Iron Content of a Moringa (Moringa oleifera) and Soy-Based Cereal (Keloreal) for Anemia Prevention in Adolescent Girls in Indonesia - Intiyati, Ani; Hafid, Fahmi; Taufiqurrahman, Taufiqurrahman; Amsal, Amsal; Segaran Balan, Santhra; Nurdiana, Shafa; Edi, Imam Sarwo; Pengge, Nuning Marina (Media Publikasi Cendekia Indonesia, 2025)
The prevalence of anemia in Indonesian adolescent girls reaches 15.5%. Blood supplement tablets are still not accepted by young women. This study was conducted to evaluate the acceptability and iron content of Keloreal. An experimental method was applied, utilizing a hedonic scale to assess attributes of taste, aroma, color, and texture, and the Atomic Absorption Spectrophotometry (AAS) method to determine iron content in the best formula. Data were analyzed using the Kruskal-Wallis test, followed by the Mann-Whitney test. The MS0 formulation received the highest overall hedonic scores. However, among the two treatment formulations, MS2 was more acceptable to the panelists due to its milder bitterness and less prominent moringa flavor, leading to better acceptance compared to MS1. Iron levels measured using the Atomic Absorption Spectrophotometry (AAS) method were 0.0596 mg/g for the MS2 formulation and 0.0756 mg/g for the control (MS0). Despite the lower iron concentration, MS2 is considered a potential alternative snack due to its elevated levels of complementary micronutrients that play a synergistic role in supporting iron metabolism and erythropoiesis.